DESCRIPTION OF A NEW METHOD OF MEASURING THE PELVIC INCIDENCE ANGLE THROUGH COMPUTED TOMOGRAPHY - DAHER,MURILO TAVARES (2020)
ABSTRACT Objective To describe a more accurate method for measuring the pelvic incidence angle using computed tomography, without the influence of the positioning of the pelvis in relation to the X-ray tube. Methods Thirteen CT scans of the lumbosacral region, abdomen or pelvis were randomly assessed, as all these exams include the sacrum and femoral heads. All the exams were performed in multichannel devices with six channels. The technique of overlapping images, already common in other musculoskeletal exams, such as TT-TG, was used. The centered sagittal cut of the left femoral head, the center of S1, and the right femoral head were used. From these, a fourth image was created, analogous to an X-ray of the pelvis, from which measurements were taken using the dedicated software. Results Of the thirteen exams, three were of the lumbar spine and 10 were of the total abdomen, six of them being of males.. The mean age was 56 years. The mean PI was 45°, ranging from 31 to 81 degrees. Among the women, the mean was 52° (31 to 81°) and among the men, 38° (32 to 46°). Conclusion CT can be used to calculate the PI, using the technique of overlapping images common to other musculoskeletal exams, such as TT-TG. Level of Evidence IIIB. Diagnostic study; Retrospective study.